Analisa Fundamental Perusahaan Pada Investasi Kode Saham TLKM - Denny Erica; Irwin Ananta Vidada; Hoiriah (LPPM Universitas Bina Sarana Informatika, 2022)
PT Telkom Indonesia (Persero) Tbk with the stock code TLKM, is one of the State-Owned Enterprises (BUMN) which has a fairly long journey from 1995 until now it is listed on the Indonesia Stock Exchange (IDX). Investors will see the company's growth from the premium, disagio, and company fundamentals before making a decision to buy and sell company shares. So starting from this this research will analyze the premium, disagio, and fundamentals of the TLKM Stock Code with data taken from PT Telkom Indonesia (Persero) Tbk, the Indonesia Stock Exchange (IDX) or the Indonesia Stock Exchange (IDX), Ipot Applications from PT Indo Premier Sekuritas, and the Stockbit Application from PT Stockbit Sekuritas. After that, the data will be continued in the premium and disagio analysis process as well as financial ratios using financial ratio analysis and other procedures using arithmetic calculation techniques that can be interpreted in the form of an economic translation and explanation related to the company's fundamentals. Keywords: Fundamentals, Investment, Stock